2012
DOI: 10.1038/mp.2012.140
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor D1 and postsynaptic density gene variants associate with opiate abuse and striatal expression levels

Abstract: Opioid drugs are highly addictive and their abuse has a strong genetic load. Dopamine-glutamate interactions are hypothesized to be important for regulating neural systems central for addiction vulnerability. Balanced dopamine-glutamate interaction is mediated through several functional associations, including a physical link between discs, large homolog 4 (Drosophila) (DLG4, PSD-95) and dopamine receptor 1 (DRD1) within the postsynaptic density to regulate DRD1 trafficking. To address whether genetic associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Multiple genomic studies in patients have revealed associations between single-nucleotide polymorphisms in the human HOMER1 gene with a variety of psychiatric disorders including schizophrenia [128, 129], autism spectrum disorder [130], major depressive disorder [131], suicide attempt [132, 133], cocaine dependence [134], and opiate abuse [135], although these genetic associations are not conclusive, requiring further replication. Meanwhile, functional studies in rodents point toward a major role for Homer1a in pathological processes related to neuropsychiatric disorders [122, 136] and antidepressant action [137, 138], including its induction in limbocorticostriatal circuits; the same circuits responsible for mediating cognitive and emotional functions in humans [139].…”
Section: Implications For Psychiatric Disordersmentioning
confidence: 99%
“…Multiple genomic studies in patients have revealed associations between single-nucleotide polymorphisms in the human HOMER1 gene with a variety of psychiatric disorders including schizophrenia [128, 129], autism spectrum disorder [130], major depressive disorder [131], suicide attempt [132, 133], cocaine dependence [134], and opiate abuse [135], although these genetic associations are not conclusive, requiring further replication. Meanwhile, functional studies in rodents point toward a major role for Homer1a in pathological processes related to neuropsychiatric disorders [122, 136] and antidepressant action [137, 138], including its induction in limbocorticostriatal circuits; the same circuits responsible for mediating cognitive and emotional functions in humans [139].…”
Section: Implications For Psychiatric Disordersmentioning
confidence: 99%
“…ISHH was performed on 20-μM coronal cryosections of human or rodent amygdala specimens as previously described (38). The high quality of the postmortem human brain samples suitable for mRNA expression studies is evident in our ability to routinely detect mRNAs of various genes in these samples (21,40,53,54).…”
Section: Ishhmentioning
confidence: 99%
“…Postmortem analysis revealed the regulatory effects of DRD1 variation on its mRNA expression in the striatum, which were blunted by chronic opioid abuse (Kauer and Malenka, 2007). Our results demonstrate that a genetic change in DRD1 is linked to heroin dependence in humans, and extends the list of variants that may affect the development of heroin dependence (Jacobs et al, 2013;Peng et al, 2013).…”
Section: Discussionmentioning
confidence: 67%
“…However, few studies have examined the association between the DRD1 gene and opiate addiction. A study by Jacobs et al (2013) found that polymorphisms in the DRD1 gene were associated with opiate addiction, despite significant differences in the racial makeup of individual samples. Another study found that DRD1 gene rs5326 was associated with heroin dependence in African Americans, whereas the association was not significant after correction for multiple testing (Levran et al, 2009).…”
Section: Introductionmentioning
confidence: 99%